Government instability shifts skin tone representations of and intentions to vote for political candidates. [article]. - Stern, Chadly
Does government stability shift the way White and Black Americans represent and make voting decisions about political candidates? Participants judged how representative lightened, darkened, and unaltered photographs were of a racially ambiguous candidate ostensibly running for political office (Studies 1-3). When the government systems was presented as stable, White participants who shared (vs. did not share) the candidates' political beliefs rated a lightened photo as. more representative of the candidate, and Black participants who shared (vs. did not share) the candidate's political beliefs rated a darkened photo as more representative (Studies 1-3). However, under conditions of instability, both Whites and Blacks who shared (vs. did not share) the candidate's political beliefs rated a lightened photo as more representative (Study 3). Representations of (Studies 2 and 3) and actual differences in (Studies 4a and 4b) skin tone predicted intentions to vote for candidates, as a function of government stability and participants' race. Further evidence suggested that system stability shifted the motivation that guided voting decisions (Study 4a and 4b(. When the system was stable, the motivation to enhance one's group predicted greater intentions to vote for lighter skinned candidates among Whites, and greater intentions to vote for darker skinned candidates among Blacks. When the system was unstable, however, lacking confidence in the sociopolitical system predicted intentions to vote for lighter skinned candidates among both Whites and Blacks. Implications for political leadership and social perception are discussed. -- (from the authors)